Cover Image, Volume 15, Issue 2 - Javan Nikkhah, Sousa; Vandichel, Matthias (Wiley interdisciplinary reviews. Computational molecular science, 2025)
The cover image is basThe cover image is based on the article Dissipative Particle Dynamics Modeling in Polymer Science and Engineering by Sousa Javannikkhah et al., https://doi.org/10.1002/wcms.70018 image